Blending e-tandem learning: Developing Speaking Competence In English Language Teaching. - Huilca Centeno, Clara Elizabeth (2022)
Blending learning has caused a huge impact on education because it permits the combination between the traditional classes and online activities. Researches have demonstrated that the application of this teaching method has had impact results especially in developing the oral English skill. For this reason, the main objective of this research was to analyze pre-service English teacher’s opinions about their participation in the e-tandem learning to develop speaking competence. The research was qualitative. Data were collected by using three focus groups. The researcher made a questionnaire for the interview and it was validated and applied. So, the students answered thirteen questions related with the problems, needs, and perspectives during virtual sessions in the e-tandem program. As result, students had English speaking limitations and lack of cultural knowledge. Based on this, the researcher designed a handbook with activities that follow the PDP Framework. These activities will help to improve the English oral abilities. The proposal was validated by experts and users and also it was divided in three units and two lesson for each level. As a conclusion, the researcher suggests to use the present handbook as a material to plan virtual conversations with English language speakers.